Is there any progress in routine management of lung cancer patients? A comparative analysis of an institution in 1996 and 2006 - Debevec, Lučka (Radiology and oncology (Ljubljana), 2009)
Background. The aim of the study was to establish eventual progress in routine management of lung cancer patients over a ten-year period at University Clinic for Respiratory and Allergic Diseases Golnik, Slovenia, comparing the results of analysis of 345 patients, diagnosed in 1996 (with analysis performed in 2002), and 405 patients, diagnosed in 2006 (with analysis performed in 2008).Patients and methods. The patients of both analysed groups were of comparable age and number of patients in stage I and II, but there were relatively more females, patients with better performance status, more precise clinical staging and tumour histology in the 2006 group. The parameters used for assessing the progress of management were as follows: time period from admittance to diagnosis and to surgery; precision of staging; accordance of clinical and pathological staging in resected patients; percentage of exploratory thoracotomy; and use of new treatment modalities. The proportion of patients in selected/actual primary treatment modality and survival rate could also be used for assessing the progress. Results. Althoughunessential longer time from admittance to microscopic confirmed diagnosis increased from a mean 7.4 to 8.6 days in 2006 progress was established by the following: more precise clinical staging (stage I and II also A and B stage, TNM staging also in small-cell lung cancer patients); improved accordance with clinical and pathological staging in resected patients (46% against 58%); decreased percentage of exploratory thoracotomy (13% against 4%); increased use of multimodality therapy as primary treatment modality (radiotherapy/chemotherapy, neoadjuvant chemotherapy); newly performed radio frequency tumour ablation. The proportion in selected/actual surgery increased from 76% to 93% and median survival rate of all patients from 6.2 to 10.6 months. (Abstract truncated at 2000 characters)
Keywords: Časovni faktorji; Diagnosis; Lung Neoplasms; Neoplasm Staging; Novotvorba, stadij; Oncology Service, Hospital; onkologija; Onkološka služba bolnišnice; pljuča; Pljučne novotvorbe; pljučni rak; preživetje; Preživetje, analiza; rak (medicina); Survival Analysis; Therapy; Time Factors; zdravljenje